The factors of intention to leave the organization among the employees at SIRIM Berhad / Noorizma Kasim - Kasim, Noorizma (Faculty of Business and Management, 2012)
This study is based on the factor of intention to leave the organization among the employee. Within this study, the factors that contribute to the intention to leave the organization among the employee can be identifying. So, when the problem can identify, this study will can help the organization to overcome that problems. Intention to leave the organization is when the employees have intention to stay or leave the organization whether they get a better offer from the other organization or the others reason. In this study, I will discuss about why the employees have intention to leave their organization. That reason we can see on the human resources practices. This is because the previous study that conducts by Ruwan Abeysekera (2007) has study about the impact of human resources practice on marketing executive turnover in Sri Langka. According to Ruwan Abeysekera (2007) the human resources practice that give the impact to the intention to leave the organization among the employees are career development, work family balance, supervisor support and compensation. Career development is typically defined as an on-going series of stages characterized by unique concerns, themes and tasks. A common underlying assumption behind these stage models of career development is that there is a series of predictable tasks that happen at more or less predictable times during the course of a career (O’Neil and Bilimoria, 2005). Work family balance also gives impact to the intention to leave among the employee in the organization. Especially for the women worker, when they feel that they don’t enough time to their family they will have an intention to leave the organization. Burchell (2002), state that globalization, downsizing, and flexible work patterns have left many employees with a feeling of increasing work demands and pressure, and a daily struggle to manage their work and family responsibilities. Employees always need their supervisor support to make the best performance. When they feel they always get attention they will always feel important and high confidence to make the job. When the employees feel satisfaction they don’t feel stress toward their responsibility on jobs. This is support by Firth, Mellor, Moore, & Loquet, (2004). From their research they found that emotional support from supervisors and self-esteem mediated the impact of stressors on stress reactions, job satisfaction, commitment to the organization and intention to quit. It is suggested that to ameliorate intention to quit and in turn reduce turnover, managers need to actively monitor workloads and the relationships between supervisors and subordinates. Monitoring workloads and supervisor-subordinate relationships by management may reduce intention to quit and subsequent turnover, thereby saving organizations the considerable financial cost and effort involved in the recruitment, induction and training of replacement staff. For the last impact in this study is compensation. Many employees want to get better life with the amount that offer by the organization. When they get better offer from the other company they will have intention to leave the organization. With the economy conditions nowadays, they will think of compensation that provide by the other company. According to Society for Human Resource Management (SHRM,2007), state that pay and satisfaction with pay is of great importance to employees.